Princess Grace of Monaco - O'Shei, Tim. (Mankato, Minn. : Capstone Press, 2009)
Describes the life of Grace Kelly, discussing her childhood in America, acting career, marriage to Prince Ranier III, duties as the princess of Monaco, and death.
Includes bibliographical references (p. 31) and index.
3.7
5-8
Keywords: Grace, -- Princess of Monaco, -- 1929-1982 -- Juvenile literature; Princesses -- Monaco -- Biography -- Juvenile literature; Motion picture actors and actresses -- United States -- Biography -- Juvenile literature; Grace, -- Princess of Monaco, -- 1929-1982.; Princesses; Women -- Biography; Motion picture actors and actresses; Grace, -- Princess of Monaco, -- 1929-1982.; Princesses -- Biography; Women -- Biography; Actors -- Biography